Qr-Code Berbasis Android Untuk Aplikasi Optimalisasi Presensi Asisten Laboratoriur - Muji Lestari; Hendra Kurniawan; Sri Karnila; Neni Purwati; Novi Herawadi Sudibyo (Jurnal SIMADA (Sistem Informasi dan Manajemen Basis Data), 2022)
Laboratory assistant attendance system used to calculate lab assistant attendance. This system uses his Android based on his QR code. Operationally, the instructor can access the scans via her QR. The purpose of this study was to alleviate problems such as attendance, accumulation of attendance documents, and calculation of the number of laboratory assistants. The method of this study used the RUP (Rational Unified Process) method in the design using UML (Unified Modeling Language). The programming languages used are PHP and HTML and the use of the MYSQL database. As a result of this research, the number of commuting assistants was calculated by the system, so the calculation could be simplified. Keywords: Attendance System; Laboratory Assistant; System QR-Code; Android